2015
DOI: 10.1371/journal.pone.0121620
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Risk Factors to Predict High On-Treatment Platelet Reactivity and Outcome in Patients with Stable Coronary Artery Disease (PREDICT-STABLE)

Abstract: ObjectivesThis study was designed to identify the multivariate effect of clinical risk factors on high on-treatment platelet reactivity (HPR) and 12 months major adverse events (MACE) under treatment with aspirin and clopidogrel in patients undergoing non-urgent percutaneous coronary intervention (PCI).Methods739 consecutive patients with stable coronary artery disease (CAD) undergoing PCI were recruited. On-treatment platelet aggregation was tested by light transmittance aggregometry. Clinical risk factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 49 publications
0
33
1
2
Order By: Relevance
“…In the present study, however, we found no effect of age, sex, type 2 diabetes mellitus, prior myocardial infarction, smoking, or body mass index on any end points. This result conflicts with recent articles showing the influence of clinical risk factors on major adverse cardiovascular events in patients on dual‐antiplatelet therapy with aspirin and clopidogrel …”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In the present study, however, we found no effect of age, sex, type 2 diabetes mellitus, prior myocardial infarction, smoking, or body mass index on any end points. This result conflicts with recent articles showing the influence of clinical risk factors on major adverse cardiovascular events in patients on dual‐antiplatelet therapy with aspirin and clopidogrel …”
Section: Discussioncontrasting
confidence: 87%
“…This result conflicts with recent articles showing the influence of clinical risk factors on major adverse cardiovascular events in patients on dual-antiplatelet therapy with aspirin and clopidogrel. 36,37 The low event rate may partly explain our results because only 5.9% of patients in the fourth aggregation quartile reached the primary end point, which was considerably lower than the expected 15% used in our sample size calculation. We used classical clinical end points, and despite studying a group of stable CAD patients with a high-risk clinical profile, our study had lower event rates than comparable studies.…”
Section: Discussionmentioning
confidence: 75%
“…PR in patients on P2Y 12 inhibitors undergoing PCI was strongly influenced by clinical risk variables such as age, BMI, diabetes mellitus, serum creatinine, and left ventricular function. 28 An inverse trend for the correlation between PR and markers for renal function, creatinine, and urea was also found in patients with critical limb ischemia.…”
mentioning
confidence: 89%
“…As regards novelty, the PREDICT score have has already been used in clopidogrel studies. 8,25,26 Notably, CYP2C19 activity has not been evaluated in those papers. On the other hand, Geisler et al have reported on the correlation between CYP2C19 polymorphism and non-genetic risk factors (PREDICT score) with high residual platelet reactivity (RPA) in patients with symptomatic coronary artery disease subjected to percutaneous coro-nary intervention.…”
Section: To Editormentioning
confidence: 99%